2013
DOI: 10.1111/jnc.12462
|View full text |Cite
|
Sign up to set email alerts
|

A conserved sequence in calmodulin regulated spectrin‐associated protein 1 links its interaction with spectrin and calmodulin to neurite outgrowth

Abstract: Calmodulin regulated spectrin-associated protein 1 (CAMSAP1) is a vertebrate microtubule-binding protein, and a representative of a family of cytoskeletal proteins that arose with animals. We reported previously that the central region of the protein, which contains no recognized functional domain, inhibited neurite outgrowth when over-expressed in PC12 cells [Baines et al., Mol. Biol. Evol. 26 (2009), p. 2005]. The CKK domain (DUF1781) binds microtubules and defines the CAMSAP/ssp4 family of animal proteins (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…The highest scoring hit in this screen was the spectraplakin ACF7 ( Fig. 2A), whereas no peptides that were derived from spectrin, which has been previously reported to bind to CAMSAP1 (King et al, 2014), were found. Whether this was owing to the absence of appropriate spectrin isoforms in HEK293T cells, the biochemical procedure used or the lack of interaction between CAMSAP3 and spectrin is unclear.…”
Section: Acf7 Binds To Camsap3 and Participates In Its Apical Recruitmentioning
confidence: 88%
See 1 more Smart Citation
“…The highest scoring hit in this screen was the spectraplakin ACF7 ( Fig. 2A), whereas no peptides that were derived from spectrin, which has been previously reported to bind to CAMSAP1 (King et al, 2014), were found. Whether this was owing to the absence of appropriate spectrin isoforms in HEK293T cells, the biochemical procedure used or the lack of interaction between CAMSAP3 and spectrin is unclear.…”
Section: Acf7 Binds To Camsap3 and Participates In Its Apical Recruitmentioning
confidence: 88%
“…Experiments in Caco-2 cells, a human intestinal cancer cell line, have demonstrated that the first coiled-coil region of CAMSAP3 is involved in recruitment of CAMSAP3-bound microtubule minus ends to the apical side (Toya et al, 2016). In CAMSAP1, this coiled-coil region was shown to bind to spectrin (King et al, 2014). Whether the apical localization of CAMSAP3, indeed, depends on spectrin or some other proteins has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Although this result may reveal a difference in the biological function of Drosophila vs. mammalian proteins, it is possible that the knockdown of all three CAMSAPs may be needed to uncover a mitotic phenotype. CAMSAPs also have been reported to interact biochemically with spectrins (an activity from which the CAMSAPs derive their name), and overexpression studies have suggested that this interaction may be important in vivo (27). However, evidence supporting a physiological connection of this protein family with spectrin is less clear than their role in regulating MT minus-ends.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Takeichi and coworkers (24,25) have shown that a homologous protein, which they termed Nezha, anchors minus-ends of MTs in cell-cell adherens junctions. The protein family was also identified through a spectrin binding activity and named calmodulin-regulated spectrin-associated protein (CAMSAP) (26,27). Bioinformatic analyses suggest that this protein family first evolved in metazoans; invertebrates possess a single gene whereas vertebrates possess three CAMSAP genes (CAMSAP1, CAMSAP2, and CAMSAP3/Nezha; Fig.…”
mentioning
confidence: 99%
“…The CC1 domain of CAMSAP1 has been reported to interact with βII-spectrin (25). The amino acid sequence crucial for this interaction within the CC1 domain was identified as LEEK (25), and this sequence with additional R (i.e., LEEKR) is conserved in CAMSAP3 (Fig.…”
Section: Significancementioning
confidence: 99%